Increased protein content of chickpea (Cicer arietinum L.) inoculated with arbuscular mycorrhizal fungi and nitrogen-fixing bacteria under water deficit conditions - Oliveira, Rui S; Carvalho, Patrícia; Marques, Guilhermina; Ferreira, Luís; Nunes, Mafalda; Rocha, Inês; Ma, Ying; Carvalho, Maria F; Vosátka, Miroslav; Freitas, Helena (Journal of the science of food and agriculture, 2017)
BACKGROUND: Chickpea (Cicer arietinum L.) is a widely cropped pulse and an important source of proteins for humans. In Mediterranean regions it is predicted that drought will reduce soil moisture and become a major issue in agricultural practice. Nitrogen (N)-fixing bacteria and arbuscular mycorrhizal (AM) fungi have the potential to improve plant growth and drought tolerance. The aim of the study was to assess the effects of N-fixing bacteria and AM fungi on the growth, grain yield and protein content of chickpea under water deficit. RESULTS: Plants inoculated with Mesorhizobium mediterraneum or Rhizophagus irregularis without water deficit and inoculated with M. mediterraneum under moderate water deficit had significant increases in biomass. Inoculation with microbial symbionts brought no benefits to chickpea under severe water deficit. However, under moderate water deficit grain crude protein was increased by 13%, 17% and 22% in plants inoculated with M. mediterraneum, R. irregularis and M. mediterraneum + R. irregularis, respectively. CONCLUSION: Inoculation with N-fixing bacteria and AM fungi has the potential to benefit agricultural production of chickpea under water deficit conditions and to contribute to increased grain protein content. © 2017 Society of Chemical Industry.
Keywords: drought; voda; Water; grain legume; očkovadla agrotechnická; dusík; Bacteria; mykorhiza; Symbiosis; symbióza; Nitrogen; Plant Proteins; Bacterial Physiological Phenomena; Mycorrhizae; Mesorhizobium mediterraneum; fyziologie bakterií; rostlinné proteiny; houby; Rhizophagus irregularis; Agricultural Inoculants; Fungi; Cicer; grain protein content